Development of Ornamental Fish Cultivation to Support Fisheries Tourism In The Sari Nadi Group, Marga District, Tabanan, Bali - Suryani S.A.M.Putri; , I G.A.D.Seri Rejeki (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Koi fish (Cyprinus carpio) is one of the ornamental fish that has a beautiful body shape and color so it has high economic value. Indicators of beauty in ornamental fish can be seen in the brilliant color, physical shape and completeness, behavior, and health conditions or stamina. These koi fish are often used as aquarium decorations and are art consumption for enthusiasts. The beauty of the color of Koi fish is in demand by the community so that farmers need to maintain the color of ornamental fish by providing feed that contains color pigments. Carotenoids are the main natural components that make up color pigments, which have a good effect on red and orange colors. Sources of carotenoids can come from spirulina which contains phycocyanin, chlorophyll-a, and carotene. Carotene is composed of xantophyll (37%), carotene (28%), and zeaxanthin (17%). Providing a source of color pigment in fish feed is one of the efforts made to get a bright color that is evenly distributed in fish. Feeding containing 8% spirulina was effective in increasing color pigmentation in the red swordtail (Xiphophorus helleri). The addition of 1.2% spirulina flour to artificial feed gave a very significant effect on increasing color intensity and was the highest result in increasing color intensity of Koi fish.